Combined complement and coagulation activation in ST-elevation myocardial infarction: associations with myocardial injury and dysfunction - Kluge, Karsten E.; Halvorsen, Sigrun; Andersen, Geir Ø.; Hansen, Charlotte H.; Seljeflot, Ingebjørg; Tønnessen, Theis; Lunde, Ida G.; Helseth, Ragnhild (Frontiers in Immunology, 2025)
IntroductionPreclinical data indicates reciprocal activation of the complement system and the coagulation cascade. The magnitude of this interaction in patients with acute myocardial infarction is unknown. We aimed to determine associations between circulating markers of complement and coagulation activation in patients with acute ST-elevation myocardial infarction (STEMI), and explore a possible link to myocardial injury and left ventricular dysfunction.Materials and methodsWe included 864 patients with STEMI. Blood was drawn at a median of 18 hours after percutaneous coronary intervention. Complement activation was assessed by the terminal complement complex (TCC), and coagulation activation by prothrombin fragment 1 + 2 (F1 + 2), D-dimer and endogenous thrombin potential (ETP). Myocardial injury was estimated by peak troponin T (TnT), and left ventricular function was quantified on echocardiography by left ventricular ejection fraction (LVEF).ResultsTCC was weakly correlated to F1 + 2 (r=0.086, p=0.012), D-dimer (r=0.176, p<0.001) and ETP (r=0.144, p<0.001). In multivariate binary logistic regression, there was no significant interaction between TCC and the coagulation markers on the risk of having high peak TnT or low LVEF.ConclusionIn this STEMI cohort, complement activation as measured by TCC was weakly associated with markers of coagulation activation, but the measured markers had no combined relation with the risk of high peak TnT or low LVEF. These findings suggest that while simultaneous activation of complement and coagulation cannot be ruled out, combined high levels of TCC and coagulation markers do not mirror the extent of myocardial injury or dysfunction in STEMI.